2018
DOI: 10.4067/s0370-41062018005001003
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre adiposidad corporal y salto horizontal en niños y adolescentes escolares

Abstract: A high level of physical fitness in childhood and adolescence is associated with more favorable physical and mental health outcomes. Objective: To compare body adiposity and horizontal jump performance with international studies and to analyze the relationship between body adiposity and horizontal jump performance indicators in children and adolescents. Patients and Method: Descriptive study conducted on 812 adolescents from Talca (Chile), with an age range between 10.0 and 16.9 years. Weight, height, waist ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
5
0
6
Order By: Relevance
“…exercises, 28 may have difficulty achieving acceptable muscle fitness values for the lower limbs. 7 Under this point of view, despite not having controlled for the patterns of physical activity of the students studied, the researchers of the present work found that the performance level of the HJ when compared with student HJ of the international studies was acceptable. Actually the Maule students participated once a week to a physical education classes performing activities related to body training, games, and sports.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…exercises, 28 may have difficulty achieving acceptable muscle fitness values for the lower limbs. 7 Under this point of view, despite not having controlled for the patterns of physical activity of the students studied, the researchers of the present work found that the performance level of the HJ when compared with student HJ of the international studies was acceptable. Actually the Maule students participated once a week to a physical education classes performing activities related to body training, games, and sports.…”
Section: Discussionmentioning
confidence: 60%
“…4 Muscle fitness is an important health indicator that is inversely and independently associated with muscle endurance, metabolic risk, inflammatory proteins, and body adiposity during childhood and adolescence. [5][6][7] It is an essential component of performance in sports. Therefore, it plays an important role in the selection of school athletes.…”
mentioning
confidence: 99%
“…Por un lado, respecto a la fuerza de prensión manual, nuestro estudio presenta valores medios similares con respecto al estudio realizado en 753 niños/as y adolescentes de 7 a 17 años de ambos sexos que entregó parámetros de normalidad en fuerzas de prensión manual realizado por Escalona et al 34 . Así como, el salto longitudinal a pies juntos, que coincide con los valores medios obtenidos en el estudio de Sepulveda et al 35 , que analizaron la relación entre adiposidad corporal y salto horizontal en 812 adolescentes entre 10 a 16,9 años, creando curvas de percentiles para estas variables en ambos sexos. Además, se identificaron diferencias significativas por sexo para la fuerza de prensión manual, concordando con los recientes estudios de Palacio-Agüero et al 36 , que estudiaron la fuerza de prensión manual, estado nutricional y obesidad abdominal en 491 adolescentes entre 10 a 17 años de 5 establecimientos educacionales de la ciudad de Santiago, mostrando mayores valores en los adolescentes varones para la fuerza de prensión manual en la mano dominante, y ambas manos.…”
Section: Discussionunclassified
“…Pues es ampliamente conocido que el aumento de nivel de la adiposidad se debe sin duda, a la adopción temprana de los modernos estilos de vida, a través del cual, alcanzan mayor IMC y perímetro de la cintura (Wardle & Boniface, 2008), además presentan elevado riesgo de desarrollar diabetes mellitus, hipertensión arterial, enfermedad arterial coronaria, síndrome metabólico (Lee, Chung, Kang, & Yu, 2012) e inclusive se asocia con variables psicológicas como la depresión, entre otras (Murabito, Massaro, Clifford, Hoffmann, & Fox, 2013). Por el contrario, adolescentes clasificados como normales o bajo peso a menudo presentan mayor fuerza muscular e inclusive son grupos físicamente más activos (Sepúlveda Cáceres et al, 2018;Gomez-Campos et al, 2019).…”
Section: Discussionunclassified